EFFECT OF PROPOLIS ON BLOOD ELECTROLYTE LEVELS OF JUVENILE RAINBOW TROUT (ONCORHYNCHUS MYKISS W. 1792) UNDER HYPDXIC STRESS - Kelestemur, Guluzar Tuna; Seven, Ismail (Agricultural Research Communication Centre, 2012)
In this study, the effect of dietary supplementation of propolis on blood electrolytes (Na+, K+, Ca+2, Mg+2, Cl-) of juvenile rainbow trout under hypoxic stress (4.5 mg/l O-2) was investigated. Three diets were prepared differing only in the type of supplementation as follows: P10 dietary group with 10 g/kg propolis, P30 dietary group with 30 g/kg propolis and control (C) dietary group with no propolis. Based on statistical evaluations, it was observed that serum Ca+ and K+ level of C group was significantly higher than NO and P30 groups (p<0.05). Serum Na+ and Cl- levels of C groups were determined to be significantly lower than P10 and P30 groups (p<0.05). Serum Mg+2 level was not statistically different among the groups (p>0.05).
Keywords: Rainbow trout; Propolis; Blood electrolytes; Hypoxia